Anthropogenic nitrogen deposition ameliorates the decline in tree growth caused by a drier climate. Issue 2 (17th January 2018) - Ibáñez, Inés; Zak, Donald R.; Burton, Andrew J.; Pregitzer, Kurt S.
Abstract: Most forest ecosystems are simultaneously affected by concurrent global change drivers. However, when assessing these effects, studies have mainly focused on the responses to single factors and have rarely evaluated the joined effects of the multiple aspects of environmental change. Here, we analyzed the combined effects of anthropogenic nitrogen (N) deposition and climatic conditions on the radial growth of Acer saccharum, a dominant tree species in eastern North American forests. We capitalized on a long‐term N deposition study, replicated along a latitudinal gradient, that has been taking place for more than 20 yr. We analyzed tree radial growth as a function of anthropogenic N deposition (ambient and experimental addition) and of summer temperature and soil water conditions. Our results reveal that experimental N deposition enhances radial growth of this species, an effect that was accentuated as temperature increased and soil water became more limiting. The spatial and temporal extent of our data also allowed us to assert that the positive effects of growing under the experimental N deposition are likely due to changes in the physiological performance of this species, and not due to the positive correlation between soil N and soil water holding capacity, as has been previously speculated in other studies. Our simulations of tree growth under forecasted climate scenarios specific for this region also revealed that although anthropogenic N deposition may enhance tree growth under a large array of environmental conditions, it will not mitigate the expected effects of growing under the considerably drier conditions characteristic of our most extreme climatic scenario.